LATE MIOCENE - PLIOCENE MAMMALIAN FAUNAS OF RUSSIA AND NEIGHBOURING COUNTRIES - Vislobokova I.; Sotnikova M.; Dodonov A. (My University, 2001)
The data on the successions of the Late Miocene - Pliocene mammalian faunas from the territory of the former Soviet Union and Mongolia are summarised. The main characteristics of the MN zone for these territories are given.
Keywords: Pliocene; Miocene; Mammal faunas; MN zones; former Soviet Union; Mongolia; Cenozoic::Neogene::Pliocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Неоген::Миоцен